2019
DOI: 10.14710/pwk.v15i1.21267
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Deforestasi Negara-Negara Di Kawasan Asia Tenggara Periode 2008-2015

Abstract: This study aims to analyze the process of changing forest area or deforestation that is multidimensional and complex, encompassing economic aspects, aspects of governance, social and demographic aspects and physical and environmental aspects represented by 15 independent variables in 10 countries in Southeast Asia in the year period 2008-2015. The analysis and study besides relying on the theoretical foundation and previous research also included several variables that describe the complexity and multidimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…As Caravaggio (2020b) proposed, governance and trade openness are vital drivers of forest cover change. Moreover, the current study revises the previous paper conducted by Handalani (2019) by employing more expanded panel data (9 countries over the period 1996 -2018). Finally, we also performed the Dumitrescu-Hulin (DH) test to examine panel causality among variables.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…As Caravaggio (2020b) proposed, governance and trade openness are vital drivers of forest cover change. Moreover, the current study revises the previous paper conducted by Handalani (2019) by employing more expanded panel data (9 countries over the period 1996 -2018). Finally, we also performed the Dumitrescu-Hulin (DH) test to examine panel causality among variables.…”
Section: Introductionmentioning
confidence: 73%
“…Thuy Van et al (2020) reported that controlling corruption has a beneficial role in achieving sustainable development. For the case of Southeast Asia, Handalani (2019) noted that the effect of corruption perceptions index (CPI) on forest cover is positive. Nonetheless, Mendes and Junior (2012) reported found that corruption has no significant impact on deforestation rates in the Amazon Rainforest in Brazil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faktanya, salah satu indeks keberhasilan proses pembangunan serta implementasi tugas dan fungsi pemerintahan di berbagai negara adalah meningkatnya kemakmuran masyarakat dan menurunnya tingkat kemiskinan. Para ahli berpendapat bahwa pembangunan pada hakikatnya merupakan interaksi yang diharapkan dapat mengubah konstruksi masyarakat serta memutus lingkaran kemiskinan yang tak berujung, seperti yang digambarkan oleh Handalani (2019) dan Freire (2013) dalam Mizal (2021). Rini & Sugiharti (2016) menekankan bahwa pembangunan bertujuan untuk memperluas aksesibilitas, menumbuhkan peruntukan kebutuhan hidup yang mendasar, meningkatkan taraf kehidupan dan mengembangkan pilihan finansial dan sosial.…”
Section: A Pendahuluanunclassified
“…Dari tabel 4 dapat diketahui bahwa tidak ada pengaruh yang positif dan signifikan antara deforestai dengan output nasional (PDB) di lima negara anggota ASEAN pada tahun 2002-2018, hal ini ditunjukan dengan nilai 𝑡 ℎ𝑖𝑡𝑢𝑛𝑔 < 𝑡 𝑡𝑎𝑏𝑒𝑙 (1.249527 < 1.99006), nilai probabilitas t-statistik 0.2153 > 0.05 dan nilai koefisien untuk variabel emisi CO2 sebesar 0.062500. Penelitian yang dilakukan oleh (Handalani, 2019) menyebutkan bahwa kerusakan hutan sebagai akibat dari proses pembangunan secara linear tidak mendorong pertumbuhan ekonomi. Penelitian lain yang dilakukan oleh (Imai dkk., 2018) menyebutkan bahwa faktor yang menjadi penyebab deforestasi terbesar di kawasan ASEAN adalah bertambahnya jumlah penduduk sehingga kebutuhan lahan untuk tempat tinggal, pembukaan pertanian sekala kecil dan perkebunan mendorong untuk membuka areal hutan.…”
Section: Uji Tunclassified